Occupational health and safety covenants : a selection of successful projects and promising shop floor initiatives (Den Haag, 2004)
"Occupational health and safety covenants are long-term cooperative agreements between branch organisations, trade unions and the government. The idea is a joint approach to improving working conditions and reducing absenteeism and the influx of people applying for benefits provided by the Disablement Benefits Act (Wet Arbeidsongeschiktheid – WAO). In other words, sector-specific solutions in which commitment and cooperation on the part of the most important players leads to excellent results. The preconditions for the approach are created by the commitment at the national level. The power of the covenants is couched in the win-win-win situation for the three involved parties. After all, the government will do all it can to turn back the WAO tide. Employers’ associations are fully aware that sick employees cost money. And employees naturally stand to gain from optimal, safe working conditions. In collective labour agreement (Collectieve Arbeidsovereenkomst - CAO) negotiations employers’ associations advocatestimulating occupational health and safety covenants and like to see effective measures included in CAOs. ..."